Maternal Involvement in Everyday Schooling: A Micro Study. (June 2015) - Panda, Gayatri
The crucial role of mothers in cultural reproduction has been widely debated since the seminal work of Basil Bernstein (1997). School education which stands as the foundation of a child's further education and future professional career relies to a great extent on the mother's role along with other important factors. The article attempts to explore micro-mothering activities contributing to children's schooling processes. This exploratory study, conducted in a village in the state of Odisha looks at the factors that influence several nuanced mothering activities in the context of mothers' differential educational qualifications and their varied locations in the caste/community and class hierarchy. The nature and extent of mothers' involvement in children's schooling was captured through interviews with 75 mothers. The study found significant instances of maternal involvement in children's schooling; the higher the level of the mother's education, the more proficient did the mothers grow, irrespective of their social origin. Educated mothers took a keen interest in their child's progress and provided concrete guidance. This does not happen in the case of the poorly educated or non-literate mothers although their love and care continues to be unquestionable!